2021
DOI: 10.1007/s00414-021-02705-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of renal glomerulosclerosis and thickness of the carotid intima-media complex as a means of age estimation in Western European bodies

Abstract: Introduction The estimation of age-at-death of unidentified cadavers is a central aspect of the identification process. With increasing age, the incidence of glomerulosclerosis and the thickness of the carotid wall have been observed to also increase. This correlation has been demonstrated in various international histological studies. The aim of our study was to assess whether these correlations also apply to a Western European population. Methodology In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Additionally, Lehmann-Leo et al measured the intima-media thickness of the common carotid artery and examined the correlation between the age and this thickness. The result suggested that the intima-media thickness of the common carotid artery was highly correlated with age (r = 0.887) [12].…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Additionally, Lehmann-Leo et al measured the intima-media thickness of the common carotid artery and examined the correlation between the age and this thickness. The result suggested that the intima-media thickness of the common carotid artery was highly correlated with age (r = 0.887) [12].…”
Section: Discussionmentioning
confidence: 96%
“…As previously mentioned, if only some body parts of an individual are found, we can estimate the person's age using several materials, such as the myocardium, abdominal aorta, and common carotid artery, with higher accuracy [12][13][14][15]. Horny et al measured the length of the abdominal aorta during autopsies before and after segment resection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations